Health and social care costs at the end of life: a matched analysis of linked patient records in East London. (16th November 2019) - Jayatunga, Wikum; Lewer, Dan; Shand, Jenny; Sheringham, Jessica; Morris, Stephen; George, Julie
Abstract: Background: care in the final year of life accounts for 10% of inpatient hospital costs in UK. However, there has been little analysis of costs in other care settings. We investigated the publicly funded costs associated with the end of life across different health and social care settings. Method: we performed cross-sectional analysis of linked electronic health records of residents aged over 50 in a locality in East London, UK, between 2011 and 2017. Those who died during the study period were matched to survivors on age group, sex, deprivation, number of long-term conditions and time period. Mean costs were calculated by care setting, age and months to death. Results: across 8, 720 matched patients, the final year of life was associated with £7, 450 (95% confidence interval £7, 086–£7, 842, P < 0.001) of additional health and care costs, 57% of which related to unplanned hospital care. Whilst costs increased sharply over the final few months of life in emergency and inpatient hospital care, in non-acute settings costs were less concentrated in this period. Patients who died at older ages had higher social care costs and lower healthcare costs than younger patients in their final year of life. Conclusions: the large proportion of costs relating to unplanned hospital care suggests that end-of-life planning could direct care towards more appropriate settings and lead to system efficiencies. Death at older ages results in an increasing proportion of care costs relating to social care than to healthcare, which has implications for an ageing society.